The analysis and structure of the closed chest injury in the thanatogenesis of multiple injuries - Fil’, Yuriy; Fil’, Andrian (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
One thousand reports about forensic medical examinations of corpses by the Lviv Regional Forensic Medical Bureau in 2002 were analysed. The chest injury took the second part in the total injury structure with the lethal outcome among injuries of other anatomical areas. Of 100 death cases, males (79) prevailed. Forty-eight people, who died from a severe combined chest injury, received the latter during road traffic accidents; 36 people died after falling down from a high place. In the above death cases, a severe chest injury was most frequently combined with a brain injury (60 %), an injury of the liver (52 %), and fractures of the extremities (49 %).